Punishing while Presuming Innocence : A Study on Bail Conditions and Administration of Justice Offences - Manikis, Marie; De Santi, Jess (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2019)
This paper examines the process and outcomes of bail hearings, focusing on cases where defendants’ hearings involved administration of justice and sentencing offences. The data analyzed for this project suggests that despite the presumption of innocence and non-punitive official objectives of judicial release, the practice by law enforcement and courts at this stage of the process tends towards punitiveness. These punitive responses are illustrated by three main findings that relate to the detention of individuals accused of administration of justice or sentencing offences, the number of conditions of release breached per combination of charges, and the breached conditions of release. These processes are understood through a durkheimian lens, using Fauconnet’s work which considers the social function of punitive processes as focused on annihilating the criminal act to establish social order. As will be seen, this function is achieved through the selection of a scapegoat that is rapidly punished, rather than appropriately assigning individual liability.